Interaction of Neisseria meningitidis carrier and disease isolates of MenB cc32 and MenW cc22 with epithelial cells of the nasopharyngeal barrier - Peters, Simon; Mohort, Katherina; Claus, Heike; Stigloher, Christian; Schubert-Unkmeir, Alexandra (Frontiers in Cellular and Infection Microbiology, 2024)
Neisseria meningitidis (Nm, the meningococcus) is considered an asymptomatic colonizer of the upper respiratory tract and a transient member of its microbiome. It is assumed that the spread of N. meningitidis into the bloodstream occurs via transcytosis of the nasopharyngeal epithelial barrier without destroying the barrier layer. Here, we used Calu-3 respiratory epithelial cells that were grown under air-liquid-interface conditions to induce formation of pseudostratified layers and mucus production. The number of bacterial localizations in the outer mucus, as well as cellular adhesion, invasion and transmigration of different carrier and disease N. meningitidis isolates belonging to MenB:cc32 and MenW:cc22 lineages was assessed. In addition, the effect on barrier integrity and cytokine release was determined. Our findings showed that all strains tested resided primarily in the outer mucus layer after 24 h of infection (>80 %). Nonetheless, both MenB:cc32 and MenW:cc22 carrier and disease isolates reached the surface of the epithelial cells and overcame the barrier. Interestingly, we observed a significant difference in the number of bacteria transmigrating the epithelial cell barrier, with the representative disease isolates being more efficient to transmigrate compared to carrier isolates. This could be attributed to the capacity of the disease isolates to invade, however could not be assigned to expression of the outer membrane protein Opc. Moreover, we found that the representative meningococcal isolates tested in this study did not damage the epithelial barrier, as shown by TEER measurement, FITC-dextran permeability assays, and expression of cell-junction components.